Hydrogen Addition to Natural Gas in Cogeneration Engines: Optimization of Performances Through Numerical Modeling - Costa, Michela; Piazzullo, Daniele; Dolce, Alessandro (Frontiers in Mechanical Engineering, 2021)
A numerical study of the energy conversion process occurring in a lean-charge cogenerative engine, designed to be powered by natural gas, is here conducted to analyze its performances when fueled with mixtures of natural gas and several percentages of hydrogen. The suitability of these blends to ensure engine operations is proven through a zero-one dimensional engine schematization, where an original combustion model is employed to account for the different laminar propagation speed deriving from the hydrogen addition. Guidelines for engine recalibration are traced thanks to the achieved numerical results. Increasing hydrogen fractions in the blend speeds up the combustion propagation, achieving the highest brake power when a 20% of hydrogen fraction is considered. Further increase of this last would reduce the volumetric efficiency by virtue of the lower mixture density. The formation of the NOx pollutants also grows exponentially with the hydrogen fraction. Oppositely, the efficiency related to the exploitation of the exhaust gases enthalpy reduces with the hydrogen fraction as shorter combustion durations lead to lower temperatures at the exhaust. If the operative conditions are shifted towards leaner air-to-fuel ratios, the in-cylinder flame propagation speed decreases because of the lower amount of fuel trapped in the mixture, reducing the conversion efficiencies and the emitted nitrogen oxides at the exhaust. The link between brake power and spark timing is also highlighted: a maximum is reached at an ignition timing of 21° Before Top Dead Center for hydrogen fractions between 10% and 20%. However, the exhaust gases temperature also diminishes for retarded spark timings. Lastly, an optimization algorithm is implemented to individuate the optimal condition in which the engine is characterized by the highest power production with the minimum fuel consumption and related environmental impact. As a main result, hydrogen addition up to 15% in volume to natural gas in real cogeneration systems is proven as a viable route only if engine operations are shifted towards leaner air-to-fuel ratios, to avoid rapid pressure rise and excessive production of pollutant emissions.